WHO/INRUD Core drug use indicators and commonly prescribed medicines: a National Survey from Sri Lanka - P. Galappatthy; P. Ranasinghe; C. K. Liyanage; M. S. Wijayabandara; S. Mythily; R. L. Jayakody (BMC, 2021)
Abstract Background Identification of internationally comparable indicators of medicines use are important for a country to implement strategies and regulations to improve usage of medicines. Sri Lanka established a new National Medicines Regulatory Authority in 2015 and this survey evaluated the medication use indicators in Sri Lanka, according to the International Network on Rational Use of Drugs (INRUD), prior to its implementation. Methods This descriptive-cross-sectional study was conducted in 80 pharmacies, representing all 25 districts of the country. Three pharmacy categories were included; privately owned pharmacies, 'Rajya Osusala' pharmacies operated by the State Pharmaceuticals Corporation (SPC) of Sri Lanka and SPC Franchisee pharmacy outlets. Selection of pharmacies from respective districts were done proportionate to estimated population. Data were collected to identify WHO/INRUD core drug use indicators and the commonly prescribed medicines. Results Total of 2328 prescriptions were included ('Rajya Osusala 559; SPC Franchise 711; private pharmacies 1058). Altogether 7,255 medicines were prescribed, and the 3 most commonly prescribed medicines were atorvastatin, losartan and metformin. Average number of medicines per encounter was 3.1±1.9 (Median: 3; range 1-12) Highest average number of medicines per encounter was reported in prescriptions received at 'Rajya Osusala' pharmacies (3.6±2.2), significantly higher than in other categories of pharmacies (p<0.001). Percentage of medicines prescribed by generic name was only 35.5%, highest at the 'Rajya Osusala' pharmacies (40.6%), significantly higher than other categories of pharmacies. The overall percentage of medicines prescribed from essential medicine list (EML) was 68.8%, without any significant variation between different categories of pharmacies. The percentage of medicines actually dispensed and accurately labelled were 92.4 and 98.5% respectively. Conclusions The average number of medicines per encounter was higher than the WHO recommended value but the usage of antibiotic and injectable drugs were within recommended standards. Generic prescribing, was very much lower. The EML prescribing, labelling and percentage dispensed medicines fared much better although lower than the WHO recommended 100% compliance. This island wide study has provided national wide data before the implementation of key changes in regulation of medicines in Sri Lanka and a repeat survey will be useful to identify impact of the new legislations.